PREFERENSI HABITAT BURUNG KUNTUL (Egretta sp.) DI DUSUN BERAN, DESA MARGODADI, KECAMATAN SEYEGAN, KABUPATEN SLEMAN, D. I. YOGYAKARTA - , ALI MAHFUD, drh. Subeno, M. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kuntul (Egretta sp.) is stated as one of the protected birds by the PP No.7 Th. 1999 due to their decreasing population. Kuntul (Egretta sp.) has special criteria in seeking for the sources as their habitat. It means that not all the sources which have suitable criteria are selected by the birds. Beran is an area located in the city of Yogyakarta which has been selected by Kuntul as their habitat. Therefore, to avoid the birds from the extinction risk, a research concerning the characteristics of Kuntulâs habitat in that area is needed to conduct. The aim of this study were to describe the biotical and physical condition of Kuntulâs habitat and to investigate the habitat preference in Beran. The methods used for collecting data were protocol sampling to collect physical data and combination method to collect biotical data. The data was taken by making transect and plot. The distance between transects was 250 m while that between plots was 200 m. Biophysical data were analyzed by using descriptive â qualitative method. Meanwhile, Neu index was used to examine the areas which being habitat preference. The research result showed that the physical condition of the area preferred by Kuntul as their habitat were: the average temperature (27.30 C), the average humidity (95.43%), the average distance between area and water sources (58.43 m), the average slopes (3.94 %), the average of rice field water height (1.29 cm), the average of rice field - mud thickness (7 cm), the average distance between area and residence (118 m), the dominant type of land use was rice field, and the total of activity in one type of land use was 1 activity. Meanwhile, the biotical condition of the area preferred by Kuntul as their habitat were: the average crown cover (32.62 %), the average grass shrub cover (64.29%), the seedlings density (0 ind/Ha), the saplings density (0 ind/Ha), the poles density (1000 ind/Ha), the trees density (1525 ind/Ha), and types of available food were grasshoppers, caterpillars, worms, and small amphibians. Lastly, the habitat preference for Kuntul in this area were located at Klakapan hamlet, Kandangan hamlet, and Beran hamlet.